Protocolo quirúrgico para el manejo interdisciplinario de caninos retenidos en el maxilar superior (2002)
ABSTRACT: One of the basic working priorities of an interdisciplinary team is to direct their efforts towards the conservation of the upper cuspid in the dental arch due to its esthetic and functional importance. Upper cuspids are the most frequently impacted teeth after third molars and in certain cases it is associated with a variable morbility. The aim of this article is to introduce to the Dental profession the treatment protocol for impacted cuspids currently used in the Maxillofacial and Stomatology Service of the University Hospital San Vicente de Paúl. The first phase is characterized by an early evaluation starting at age 8 or 9 and a clinical and radiographical follow up done by the pedodontist. If after the elimination of certain impactation factors and a six month to one year follow up the pedodontist obtains no positive results in the stimulation of cuspid eruption then the patient must be referred to the surgeon. Both surgeon and pedodontist will evaluate and choose the most appropriate surgical approach which will allow the cuspid ́s recovery. During the second phase the surgical procedure is done. The most frequently used in our practice are the palatal surgical window for palatal impaction and the apical repositioning flap for buccal impaction. The third phase is done by the Pedodontist or Orthodontist who by using removable or fixed appliances aim towards the traction and alignment of the cuspid achieving the right position in the dental arch. When the surgical extraction is indicated, we make reference to surgical approaches used for both buccal and palatal impaction.